Long non-coding RNA SNHG9 regulates viral replication in rhabdomyosarcoma cells infected with enterovirus D68 via miR-150-5p/c-Fos axis - Fu, Huichao; Si, Junzhuo; Xu, Lei; Tang, Xia; He, Yonglin; Lu, Nan; Li, Huayi; Li, Anlong; Gao, Sijia; Yang, Chun (Frontiers in Microbiology, 2023)
The epidemic of enterovirus D68 (EV-D68) has increased knowledge of the virus as a pathogen capable of causing serious respiratory and neurological illnesses. It has been shown that long noncoding RNAs (lncRNAs) regulate viral replication and infection via multiple mechanisms or signaling pathways. However, the precise function of lncRNAs in EV-D68 infection remains unknown. The differential expression profiles of lncRNA in EV-D68-infected and uninfected RD cells were studied using high-throughput sequencing technology. The results demonstrated that a total of 375 lncRNAs were highly dysregulated in the EV-D68 infection model, and the gene regulation mechanism of lncRNAs predicted the possible regulatory pathways involved in lncRNAs. In the EV-D68 infection model, the lncRNA SNHG9 (small ribonucleic acid host gene 9) and its mechanism were studied. lncRNA SNHG9 and c-Fos were increased in EV-D68-infected RD cells. However, the expression level of miR-150-5p was downregulated. In addition, overexpression of SNHG9 in RD cells resulted in decreased viral replication levels and viral titers following infection with EV-D68, and further experiments revealed that overexpression of SNHG9 inhibited the viral replication by targeting increased miR-150-5p binding and significantly increased c-Fos expression in RD cells. Our findings indicate that the SNHG9/miR-150-5p/c-Fos axis influences EV-D68 replication in host cells and that SNHG9 may be a possible target for anti-EV-D68 infection therapies.